2007
DOI: 10.1016/j.jacc.2006.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular Structure and Function in Hypertensive Participants With Heart Failure and a Normal Ejection Fraction

Abstract: As a group, HFNEF subjects have increased LV diastolic diameter and increased calculated stroke volume. They also have increased prevalence of multiple comorbidities, including anemia, renal dysfunction, and obesity, that can cause volume overload. These data suggest that extracardiac factors, via volume overload, may contribute to the pathophysiology of HFNEF in the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
117
3
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(134 citation statements)
references
References 43 publications
10
117
3
4
Order By: Relevance
“…We excluded three hypertensive patients from the present study because they had reduced EF or LV enlargement suggesting the development of LV systolic dysfunction or LV remodeling. Maurer et al 26 also described an increased LV diastolic diameter in 167 hypertensive patients with heart failure with a normal EF, a finding that is supported by our results. Rame et al 27 reported that 18% of 159 patients with DHF developed reduced EF after a follow-up of B4 years.…”
Section: Global Systolic Functionsupporting
confidence: 90%
“…We excluded three hypertensive patients from the present study because they had reduced EF or LV enlargement suggesting the development of LV systolic dysfunction or LV remodeling. Maurer et al 26 also described an increased LV diastolic diameter in 167 hypertensive patients with heart failure with a normal EF, a finding that is supported by our results. Rame et al 27 reported that 18% of 159 patients with DHF developed reduced EF after a follow-up of B4 years.…”
Section: Global Systolic Functionsupporting
confidence: 90%
“…Thus, renal insufficiency may increase the prevalence of DHF partly through the induction of anemia in hypertensive patients without reduced EF. Maurer et al concluded that anemia induced DHF through volume overload because LV end-diastolic dimension was greater in the DHF patients than in hypertensive patients without heart failure (13). However, the LV end-diastolic dimension was small in patients with renal insufficiency and low hemoglobin in this study (Table 4), and thus, anemia was unlikely to induce DHF through volume overload.…”
Section: Renal Insufficiency and Dhfmentioning
confidence: 50%
“…Previous studies have also shown that serum creatinine and the prevalence of anemia were higher in DHF patients than in hypertensive patients without heart failure (13), and anemia exacerbated the prognosis of DHF patients (32,33). Thus, renal insufficiency may increase the prevalence of DHF partly through the induction of anemia in hypertensive patients without reduced EF.…”
Section: Renal Insufficiency and Dhfmentioning
confidence: 92%
See 1 more Smart Citation
“…Although clinical classifi cation of patients with HFNEF would appear to be straightforward [6], agreement as to both etiology and pathogenesis has generated ongoing debate, as the prevailing wisdom that diastolic dysfunction explains the disorder has been repeatedly challenged [7][8][9]. The diffi culty of facile, accurate, non-invasive assessment of diastolic function adds to the controversy.…”
Section: Introductionmentioning
confidence: 99%